Steady and transient critical heat flux for subcooled water in a mini channel. (January 2017) - Shibahara, M.; Fukuda, K.; Liu, Q.S.; Hata, K.
Highlights: Transient critical heat fluxes (CHFs) for subcooled water in a small vertical tube were measured. The transient CHFs increased with decreasing period of heat generation rates and increasing flow velocity. The empirical correlation of the transient CHFs for the small tube was obtained based on the experimental data. Abstract: The transient critical heat fluxes (CHFs) were measured for water flowing in a small vertical tube with exponentially increasing heat inputs. A stainless steel tube (SUS 304) with an inner diameter of 1.0 mm and a length of 47.4 mm was used as a test tube, which was mounted vertically in the experimental water loop. In the experiment, the upward flow velocity ranged from 9.4 to 13.4 m/s and the inlet subcooling ranged from 85 to 145 K. The heat generation rate was exponentially increased as a function of Q0 exp( t / τ ). The period of the heat generation rate was ranged from 82 ms to 30 s. Experimental results indicated that the CHFs increased with decreasing period of heat generation rates and increasing flow velocity. For shorter periods of the heat generation rate, the CHFs were significantly higher. The CHFs were affected by the period of the heat generation rate and flow velocities. The empirical correlations of the transient CHFs for the small tube were obtained based on the experimental data.